Videoconference assessment of functional and cognitive measures in Brazilian older adults: a reliability and feasibility study - Juliana Daniele de Araújo Silva; Diógenes Cândido Mendes Maranhão; Natália Barros Beltrão; Breno Quintella Farah; Vinicius de Oliveira Damasceno; Bruno Remigio Cavalcante; André Luiz Torres Pirauá (Geriatrics, Gerontology and Aging, 2023)
Objective: We aimed to determine the feasibility and reliability of videoconference assessment of functional and cognitive status among older adults in the context of the COVID-19 pandemic. Methods: Thirty community-dwelling older adults (86.70% women) with a mean age of 69.77 (SD = 6.60) years who were physically independent and had no signs of cognitive impairment were included in the sample. An independent and experienced researcher assessed functional (chair rise test, chair stand test, sitting and rising test) and cognitive (Montreal Cognitive Assessment, parts A and B of the Trail Making Test, the Stroop test, the verbal fluency test) performance in real-time on the Google Meet platform on 2 non-consecutive days. The reliability of the measures was analyzed using the intraclass correlation coefficient (ICC), a paired t-test, or Wilcoxon and Bland-Altman analysis. The feasibility of the assessment was investigated using a standardized 14-item questionnaire. Results: All functional performance measures showed excellent intra-rater reliability, with ICCs from 0.90 (95%CI 0.78 - 0.95) for the sitting and rising test to 0.98 (95%CI 0.96 - 0.99) for the chair rise test. Our analysis also showed mixed levels of reliability across measures, including good ICC (ranging from 0.79 - 0.91) for the Montreal Cognitive Assessment, part B of the Trail Making Test, and the congruent and neutral trials in the Stroop test, but poor-to-moderate ICC (ranging from 0.42 - 0.58) for the other cognitive assessments. In general, the participants reported good feasibility for the assessment format. Conclusion: In healthy and highly educated older adults, videoconferencing is a feasible method of determining functional and cognitive performance. Functional measures showed excellent reliability indexes, whereas cognitive data should be interpreted carefully, since the reliability varied from poor to moderate.